Impaired Structural Network Properties Caused by White Matter Hyperintensity Related to Cognitive Decline - Yang, Dan; Huang, Lili; Luo, Caimei; Li, Mengchun; Qin, Ruomeng; Ma, Junyi; Shao, Pengfei; Xu, Hengheng; Zhang, Bing; Xu, Yun; Zhang, Meijuan (Frontiers in Neurology, 2020)
Purpose: There is a high correlation between white matter hyperintensity (WMH) and cognitive impairment (CI) in elderly people. However, not all WMH subjects will develop into CI and the potential mechanism of WMH related CI is still unclear. This study aimed to investigate the topological properties of white matter structural network in WMH related CI. Methods: 41 WMH subjects with CI (WMH-CI), 42 WMH subjects without CI (WMH-no-CI) and 52 elderly healthy controls (HC) were recruited. Diffusion tensor imaging (DTI) fiber tractography and graph theoretical analysis were applied to construct the structural network. We compared network properties and clinical features among the three groups. Multiple linear regression analysis was performed to investigate the relationships among WMH volumes, impaired network properties and cognitive functions in WMH-CI group. Results: Compared with the controls, both WMH groups showed decreased network strength, global efficiency and increased characteristic path length at the level of whole brain. WMH-CI group displayed more profound impairments of nodal efficiency and nodal path length within multiple regions including precentral, cingulate and medial temporal gyrus. The disrupted network properties were associated with CI and WMH burdens in WMH-CI group. Furthermore, a mediation effect of nodal path length in left inferior frontal gyrus was observed for the association between periventricular WMH (PWMH) and memory deficit. Conclusions: Brain structural network in WMH-CI is significantly disturbed, and this disturbance is related to the severity of WMH and CI. Increased nodal path length in IFGoperc.L was shown to be a mediation framework between PWMH and WMH-related memory, which shed lights on investigating underlying mechanisms of CI caused by WMH.